A survey of the perception of well-being among emergency physicians in Taiwan - Kun-Chuan Chen; Wan-Hua Hsieh; Sheng-Chuan Hu; Pei-Fang Lai (Tzu Chi Medical Journal)
Objectives: The objective of this study is to investigate the feelings (well-being) of emergency physicians in Taiwan regarding their job and the relationship between these feelings and the work environment. Materials and Methods: A questionnaire was used to survey emergency physicians across Taiwan from January to June 2014. The questionnaire contents were categorized into five specific factors that could affect well-being, including “emergency quality, emergency safety, support environment, workload, and salary and benefits.” Well-being was rated directly on a scale of 1–10, with 10 indicating the highest level of happiness. Physician retention was also surveyed. The correlations among the five factors, well-being, and physician retention were analyzed. The five factors were quantified as a “happiness index” and compared between religious and nonreligious hospitals and medical centers and regional hospitals. Results: A total of 398 questionnaires were received, and the response rate was 39%. Of these, 42.7% of responders reported high ratings for well-being (scores of 7–10, 1 is the worse, and 10 is the best) and 40.3% felt neutral (scores of 5–6). Only 12.3% doctors did not think they would stay at the same position for the next 3 years. All five factors had moderately significant correlations with each other (γ = 0.195–0.534, γ< 0.01). All five factors also significantly correlated with well-being. Emergency safety (γ = 0.121, γ< 0.05), salary and benefits (γ = 0.143, γ< 0.05), and well-being (γ = 0.189, γ< 0.01) were correlated with physician retention. The happiness indices of emergency quality, support environment, and workload were significantly higher in regional hospitals than medical centers. Conclusions: All five indicators had impacts on well-being. The respondents reported heavy workloads, including high stress and even poorly met physiological needs. In addition, the threat of violence, salaries, and well-being correlated with physician retention. Hospital administrators can make efforts to improve the well-being of doctors and physician retention by adjusting environmental factors.